Living and health conditions of elderly people over 80 - Silva, Sabrina Piccinelli Zanchettin; Marin, Maria José Sanches; Rodrigues, Márcia Renata (Universidade Federal do Rio Grande do Sul. Escola de Enfermagem, 2015)
Objective: This article proposes to describe demographic data and health conditions of elderly people at age 80 or more.Method: Quantitative-descriptive study of 95 elderlies from five units of the Family Health Strategy in the period from September to December 2013, using script with general data of the living conditions and health, including validated scales in geriatrics and gerontology.Results: The average age was 85.4 years. There was a predominance of women. Most were widowers with family income, more frequently between 2 or 3 minimum wages and economic participation is for means of sharing responsibility. They present dependency for many of Daily Living Instrumental Activities and, on average, reported 2.2 diseases. Fear of falling, decreased vision and hearing as well as pain in different body regions are reported.Conclusion: It appears that they have more intense needs than the elderly in general, requiring new ways of organizing their health care.

Objetivo: Se propone a describir las condiciones de vida y la salud de las personas mayores de 80 años o más.Método: Estudio cuantitativo-descriptivo realizado con 95 personas de cinco unidades de la Estrategia Salud de la Familia, mediante un guión con los datos generales de las condiciones de vida y de salud, incluyendo escalas validadas en geriatría y gerontología.Resultados: La edad promedio fue de 85,4 años. Las mujeres predominaron en la mayoría de los viudos, el ingreso familiar más común es de 2-3 salarios mínimos. La dependencia actual de muchas de las actividades instrumentales de la vida diaria, en promedio 2.2 enfermedades reportadas y medicamentos utilizados 4.3 / ancianos. Mencionan el miedo de caerse, disminución de la visión, y dolor en diferentes regiones del cuerpo.Conclusión: Parece que tienen necesidades más intensas de las personas mayores en general, lo que requiere la preparación de la sociedad para cumplir con la misma eficacia.

Objetivo: Propõe-se a descrever dados sociodemográficos e as condições de saúde de idosos com 80 anos ou mais.Método: Estudo quantitativo-descritivo realizado com 95 idosos de cinco unidades da Estratégia Saúde da Família, no período de setembro a dezembro de 2013, utilizando roteiro com dados gerais das condições de vida e de saúde, incluindo escalas validadas em geriatria e gerontologia.Resultados: A média de idade foi de 85,4 anos. Houve predomínio de mulheres. A maioria viúvos com renda familiar, mais frequente, de 2 a 3 salários mínimos, e a participação econômica é a de dividir responsabilidade. Apresentam dependência para muitas das Atividades Instrumentais de Vida Diária e, em média, referiram 2,2 doenças. Referem medo de cair, diminuição da visão e da audição, além de dor em diferentes regiões do corpo.Conclusão: Depreende-se que eles apresentam necessidades mais intensas dos que os idosos em geral, demandando novas formas de organizar seu cuidado em saúde.
Condiciones de vida y salud de personas mayores de 80 anos
Condições de vida e de saúde de idosos acima de 80 anos
Keywords: Determination of health care needs; Elderly of 80 years or more; Social conditions; Determinação de necessidades de cuidados de saúde; Idoso de 80 anos ou mais; Condições sociais